Micro‐aggregates do not influence bone marrow stromal cell chondrogenesis. (2nd April 2014) - Potier, E.; Rivron, N. C.; Van Blitterswijk, C. A.; Ito, K.
Abstract: Although bone marrow stromal cells (BMSCs) appear promising for cartilage repair, current clinical results are suboptimal and the success of BMSC‐based therapies relies on a number of methodological improvements, among which is better understanding and control of their differentiation pathways. We investigated here the role of the cellular environment (paracrine vs juxtacrine signalling) in the chondrogenic differentiation of BMSCs. Bovine BMSCs were encapsulated in alginate beads, as dispersed cells or as small micro‐aggregates, to create different paracrine and juxtacrine signalling conditions. BMSCs were then cultured for 21 days with TGF β 3 added for 0, 7 or 21 days. Chondrogenic differentiation was assessed at the gene (type II and X collagens, aggrecan, TGF β, sp7) and matrix (biochemical assays and histology) levels. The results showed that micro‐aggregates had no beneficial effects over dispersed cells: matrix production was similar, whereas chondrogenic marker gene expression was lower for the micro‐aggregates, under all TGF β conditions tested. This weakened chondrogenic differentiation might be explained by a different cytoskeleton organization at day 0 in the micro‐aggregates. Copyright © 2014 John Wiley & Sons, Ltd.